2019
DOI: 10.1038/s41597-019-0197-0
|View full text |Cite
|
Sign up to set email alerts
|

Updating the global occurrence of Culicoides imicola, a vector for emerging viral diseases

Abstract: Culicoides imicola is the main vector transmitting viruses causing animal diseases such as Bluetongue, African Horse Sickness, and Schmallenberg. It has become widely distributed, with reports from South Africa to southern Europe, and from western Africa to southern China. This study presents a global compendium of Culicoides imicola occurrence between 1943 and 2018, reflecting the most recently compiled and harmonized global dataset derived from peer-reviewed literature. The procedures used in producing the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…During the last decades, various members of the Orbivirus genus, including BTV and AHSV, have expanded their geographical distribution, causing numerous infectious outbreaks in new regions where they were not endemic. Orbiviruses are transmitted by arthropod vectors, an added difficulty for their control, as climate change together with globalization contribute to the expansion of these vectors and to their establishment in new areas [ 25 , 63 , 64 ]. Orbiviruses, such as BTV and AHSV, cause serious damage to animal health and have a significant economic impact on society [ 9 , 23 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decades, various members of the Orbivirus genus, including BTV and AHSV, have expanded their geographical distribution, causing numerous infectious outbreaks in new regions where they were not endemic. Orbiviruses are transmitted by arthropod vectors, an added difficulty for their control, as climate change together with globalization contribute to the expansion of these vectors and to their establishment in new areas [ 25 , 63 , 64 ]. Orbiviruses, such as BTV and AHSV, cause serious damage to animal health and have a significant economic impact on society [ 9 , 23 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our results indicated that pre-treatment with ATA does not inhibit infection by BTV-4 and AHSV-4 ( Figure 3 ). The saliva of Culicoides may play a role in viral replication and transmission by recruiting leucocytes where the virus can replicate or by generating infectious subviral particles, thus enhancing particle infectivity [ 63 , 64 , 67 ]. In this study, we demonstrated that ATA is able to inhibit viral replication in insect cells ( Figure 6 ), which could be important to prevent and control the spread of these viruses through their insect vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the virus has been prevalent in tropical and subtropical regions located between 35 °S and 45 °N, which coincided with the distribution of midges from the genus Culicoides , the main vector involved in BTV transmission. However, several outbreaks in regions located further north have been reported, mainly facilitated by the recent spread of insect vectors [ 3 , 4 , 5 , 6 ]. To date, 29 serotypes of BTV have been identified [ 7 ], with two more putative serotypes and several other variants being further described.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the detection of C. brevitarsis on the New England plains provided evidence of its rare incursion and crossing the GDR [46], however as noted above, establishment of the species in the New England region cannot be ruled out. Further investigations on the role of bioclimatic variables determining the dispersal of most abundant species collected in the present study is recommended for future modelling [29,50]. Despite the greater abundance and richness of Culicoides species, the plain and slope subregions had lower diversity and evenness indices.…”
Section: Plos Onementioning
confidence: 74%